Solid-state composite phase change thermal insulation material, preparation method and application thereof
Patent Information
- Application Number
- CN202610593490.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-04-30
- Publication Date
- 2026-08-18
AI Technical Summary
基于相变过程和性能,PCMs在锂离子电池组中得到了广泛应用,PCMs已被商业应用于电池系统中,然而,传统的制备气凝胶片材的操作过程复杂、条件苛刻,且隔热性能较差
1、本发明采用溶胶-凝胶法,以廉价的无机铝盐为原料,与水溶剂均匀分散,在耐高温的陶瓷纤维毡内进行凝胶,使得氧化铝凝胶与陶瓷纤维毡复合,且将二氧化硅包覆在氧化铝凝胶骨架上,经过真空干燥,制备出轻质、高保温隔热性能的氧化铝复合相变材料,极大降低了制备复合气凝胶保温板等隔热材料的生产成本。
Smart Images

Figure CN122599609A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of solid composite phase change thermal insulation materials, and particularly to a solid composite phase change thermal insulation material, its preparation method, and its application. Background Technology
[0002] In recent years, the greenhouse effect and resource depletion have severely damaged natural ecosystems, prompting a profound understanding of the necessity for new energy reserves that improve energy efficiency. The energy selection paradigm has undergone a gradual transition from chemical fuels to electrochemical energy storage devices, and from traditional fuel vehicles to electric vehicles. The battery pack is the fulcrum of electric vehicles, directly determining their energy utilization rate and driving range. Lithium-ion batteries, due to their high energy density, powerful power output, minimal self-discharge tendency, and long lifespan, have been widely used in the automotive industry. Commercial lithium-ion batteries are characterized by a structural division between the cathode and anode, mediated by an electrolyte. The electrolyte includes organic solvents, lithium-based electrolyte salts (such as lithium hexafluorophosphate, LiPF6), and various additives. However, the volatility and flammability of organic solvents often lead to thermal runaway (TR) accidents when the internal temperature of lithium-ion batteries (LIBs) becomes too high. Therefore, exploring effective and appropriate methods to suppress the propagation of thermal runaway is essential.
[0003] Adding thermal insulation materials to battery packs is an effective way to suppress or reduce thermal runaway (TR) diffusion in lithium-ion batteries. Thermal insulation materials used in LIBs can generally be divided into two categories: phase change materials (PCMs) and barrier insulation materials. Traditional insulating materials, such as polyurethane foam, fiberglass, and ceramics, are used in LIBs. These materials can insulate a large amount of heat, but their high weight and cost limit further applications. With the continuous advancement of science and technology, researchers have begun to design and manufacture high-performance thermal insulation materials. New materials with excellent thermal insulation performance and lightweight properties, such as aerogels and porous materials, have emerged and are beginning to be used in LIBs. Compared with traditional thermal insulation materials, these new materials have lighter weight and higher thermal insulation performance, but they still have limitations in meeting practical application requirements, such as a certain degree of reduced thermal insulation performance, limited performance, and high cost.
[0004] Currently, the potential of phase change materials (PCMs) in thermal insulation and their application in energy storage technologies have garnered widespread attention from researchers. Notably, PCMs can undergo phase changes under specific conditions, thereby altering their physical properties. Based on the phase change process and performance, PCMs have been widely used in lithium-ion battery packs and are commercially applied in battery systems. However, traditional methods for preparing aerogel sheets are complex, demanding, and offer poor thermal insulation performance. With the increasing demand for lithium-ion batteries in the new energy market, the need for novel barrier-type thermal insulation materials for battery thermal management is further increasing. Researching higher-quality and easier-to-operate PCM preparation methods is beneficial for reducing the risk of thermal runaway in lithium-ion batteries and meeting the thermal insulation requirements after cell thermal runaway. Summary of the Invention
[0005] In view of the shortcomings of the prior art, the purpose of this invention is to provide a solid composite phase change thermal insulation material, its preparation method and application, thereby effectively solving the problems existing in the background art.
[0006] This invention employs a sol-gel method, using inexpensive inorganic aluminum salts as raw materials, water and ethanol as solvents, and propylene oxide (Po) as a gel initiator to induce the gelation of aluminum chloride hexahydrate solution. The prepared sol is then composited with ceramic fiber felt, vacuum-sealed using aluminum-plastic film, ultimately yielding a lightweight, low thermal conductivity, and high thermal insulation composite phase change material. The solid-state composite phase change insulation material prepared by this invention is more cost-effective and simpler in terms of process flow, possessing not only excellent thermal insulation performance but also properties of low-temperature thermal conductivity, medium-temperature heat absorption, and high-temperature thermal insulation.
[0007] To achieve the above technical objectives, the present invention adopts the following technical solution: On one hand, this invention discloses a method for preparing a solid composite phase change thermal insulation material, comprising the following steps: S1: Take inorganic aluminum salt, anhydrous ethanol and deionized water in proportion to form a mixture, and then treat the mixture with ultrasound. S2: Add gel initiator to the ultrasonically treated mixture in proportion, and stir to gel the mixture; S3: A gel plate is obtained by combining a gelled mixture with ceramic fiber felt; S4: Cover and package the gel plate with aluminum-plastic film, vacuum process it and then seal it to obtain a solid composite phase change thermal insulation material.
[0008] As a further preferred embodiment of the above technical solution: in step S1, the mass ratio of inorganic aluminum salt: anhydrous ethanol: deionized water is 4~5:5~9:3~12; preferably, the inorganic aluminum salt is aluminum chloride hexahydrate.
[0009] A further preferred embodiment is as follows: in step S1, the mass ratio of inorganic aluminum salt: anhydrous ethanol: deionized water is 4:5:12; preferably, the inorganic aluminum salt is aluminum chloride hexahydrate.
[0010] A further preferred option is that, in step S1, the ultrasonic treatment time is 1~2 hours.
[0011] As a further preferred embodiment of the above technical solution: in step S2, the gel initiator is propylene oxide, wherein the mass ratio of propylene oxide to deionized water is 5~9:3~12, preferably, the mass ratio of propylene oxide to deionized water is 5:12.
[0012] As a further preferred embodiment of the above technical solution: In step S3, the step of combining the gelled mixture with the ceramic fiber felt includes: S31: Pour the gelled mixture onto the ceramic fiber felt, so that the mixture wets the surface of the ceramic fiber felt and penetrates it evenly into its interior; S32: Let the obtained ceramic fiber felt permeated with the mixed solution stand at room temperature for 30-45 minutes to obtain a gel plate.
[0013] As a further preferred embodiment of the above technical solution: Step S4, the step of obtaining the solid composite phase change thermal insulation material includes: S41: Cover the gel plate with aluminum-plastic film and seal three sides of the gel plate with a heat sealer; S42: Place the gel plate with three sides sealed by aluminum-plastic film in a vacuum drying oven and vacuum dry for 2-9 minutes; S43: After drying, remove the gel plate and seal its fourth side with a heat sealer to complete the encapsulation, thus obtaining a solid composite phase change thermal insulation material.
[0014] On the other hand, the present invention discloses a solid composite phase change thermal insulation material, which is obtained by the preparation method described in any of the above claims.
[0015] In another aspect, this invention discloses the application of a solid composite phase change thermal insulation material in a battery insulation system.
[0016] Compared with the prior art, the present invention has the following beneficial effects: 1. This invention employs a sol-gel method, using inexpensive inorganic aluminum salts as raw materials, which are uniformly dispersed with an aqueous solvent and gelled within a high-temperature resistant ceramic fiber felt. This results in the alumina gel being composited with the ceramic fiber felt, and silica is coated onto the alumina gel skeleton. After vacuum drying, a lightweight alumina composite phase change material with high thermal insulation performance is prepared, which greatly reduces the production cost of preparing thermal insulation materials such as composite aerogel insulation boards.
[0017] 2. This invention uses alumina as a skeleton and silica as a coating on the surface of the skeleton. The role of alumina is to provide a high-temperature resistant skeleton, and silica on the surface of the skeleton can prevent large-area sintering. The final composite phase change material can still maintain good structure and thermal insulation performance under high temperature environment.
[0018] 3. The drying method of the present invention is atmospheric pressure drying, which is simple equipment and has low daily energy consumption. Most existing methods use supercritical drying, which avoids the disadvantages of complex operation and harsh conditions.
[0019] 4. The solid-state composite phase change thermal insulation material prepared by this invention, compared with existing thermal insulation materials, not only has excellent high-temperature thermal insulation performance but also low-temperature thermal conductivity, ensuring that the temperature of the battery cells within the modules remains relatively balanced, thus solving the problem of uneven temperature distribution among the battery cells within the modules. It also possesses mid-temperature heat absorption properties; when a single battery cell in the module exceeds room temperature, the material undergoes a phase change, absorbing most of the heat generated by the battery cell. Therefore, the phase change material of this invention can maintain temperature balance between battery modules before thermal runaway, significantly reducing the risk of thermal runaway and meeting the thermal insulation requirements after thermal runaway. Attached Figure Description
[0020] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the accompanying drawings used in the description of the embodiments or the prior art will be briefly introduced below.
[0021] Figure 1 This is a flowchart of a method for preparing a solid composite phase change thermal insulation material according to the present invention; Figure 2 This is a state diagram of the phase transition process of the solid composite phase change gel of the present invention at high temperature; Figure 3 This is a finished product image of the solid-state composite phase change heat insulation sheet of the present invention; Figure 4 This is a STA diagram of the solid composite phase change thermal insulation material of the present invention; Figure 5 This is a diagram showing the hot and cold surfaces of the solid composite phase change thermal insulation material of the present invention; Figure 6 This is a temperature difference diagram of the upper cold and hot surfaces of the solid composite phase change thermal insulation material of the present invention; Figure 7 This is a comparison diagram of the temperature difference between the hot and cold surfaces of the solid composite phase change thermal insulation material of the present invention and other materials; Figure 8 This is a schematic diagram of the equipment used in the thermal spread experiment of the composite phase change thermal insulation material prepared in this invention. Figure 9 A schematic diagram of the thermal runaway testing device for the composite phase change thermal insulation sheet prepared in this invention. Figure 10 This diagram illustrates the thermal propagation suppression effect of the composite phase change thermal insulation material prepared according to the present invention. Detailed Implementation
[0022] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are some embodiments of the present invention, but not all embodiments.
[0023] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Any stated value or intermediate value within a stated range, as well as each smaller range between any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.
[0024] Reference Figures 1-10 This invention addresses the problem that when a short circuit occurs inside or outside a power battery, the battery releases a large amount of heat in a short time, causing a rapid temperature rise. A single thermally runaway battery can then trigger thermal runaway in nearby batteries through heat conduction and flame, leading to thermal runaway of the entire battery module / pack and potentially causing fires or explosions in new energy vehicles. The solid-state composite phase change thermal insulation material prepared using the method of this invention can maintain the temperature balance between battery modules before thermal runaway, significantly reducing the risk of thermal runaway and meeting the thermal insulation requirements after thermal runaway.
[0025] Example 1: The present invention discloses a method for preparing a solid composite phase change thermal insulation material, comprising the following steps: 1) Mix aluminum chloride hexahydrate, anhydrous ethanol, and deionized water in a beaker at a mass ratio of 4:5:12 to form a mixture, and then hydrolyze by ultrasonic stirring for 1-2 hours. 2) Add propylene oxide to the ultrasonically treated mixture, with a mass ratio of propylene oxide to deionized water of 5:12. Stir for 1-3 minutes and then stop to allow the mixture to gel. 3) Pour the gelled mixture onto the ceramic fiber felt, allowing the mixture to wet the surface of the ceramic fiber felt and penetrate evenly into its interior. Let it stand at room temperature for 30-45 minutes to obtain a gel plate. 4) Cover the gel plate with aluminum-plastic film and seal three sides of the gel plate with a heat sealer. Then place the gel plate with the aluminum-plastic film-sealed three sides in a vacuum drying oven, vacuum dry for 3 minutes, take it out, and seal the fourth side of the gel plate with a heat sealer to complete the encapsulation, thus obtaining a solid composite phase change thermal insulation material of alumina and ceramic fiber felt.
[0026] The solid composite phase change thermal insulation material prepared in this embodiment is as follows: Figures 2-3 As shown, subsequent experiments were conducted using the materials prepared in this embodiment.
[0027] Example 2: 1) Mix aluminum chloride hexahydrate, anhydrous ethanol, and deionized water in a beaker at a mass ratio of 4:7:3 to form a mixture, and then hydrolyze by ultrasonic stirring for 1-2 hours. 2) Add propylene oxide to the ultrasonically treated mixture, with a mass ratio of propylene oxide to deionized water of 6:3. Stir for 1 to 3 minutes and then stop to allow the mixture to gel. 3) Pour the gelled mixture onto the ceramic fiber felt, allowing the mixture to wet the surface of the ceramic fiber felt and penetrate evenly into its interior. Let it stand at room temperature for 30-45 minutes to obtain a gel plate. 4) Cover the gel plate with aluminum-plastic film and seal three sides of the gel plate with a heat sealer. Then place the gel plate with the aluminum-plastic film-sealed three sides in a vacuum drying oven and vacuum dry for 5 minutes. Take it out and seal the fourth side of the gel plate with a heat sealer to complete the encapsulation, and obtain a solid composite phase change thermal insulation material of alumina and ceramic fiber felt.
[0028] Example 3: 1) Mix aluminum chloride hexahydrate, anhydrous ethanol, and deionized water in a beaker at a mass ratio of 4:9:12 to form a mixture, and then hydrolyze by ultrasonic stirring for 1-2 hours. 2) Add propylene oxide to the ultrasonically treated mixture, with a mass ratio of propylene oxide to deionized water of 9:12. Stir for 1-3 minutes and then stop to allow the mixture to gel. 3) Pour the gelled mixture onto the ceramic fiber felt, allowing the mixture to wet the surface of the ceramic fiber felt and penetrate evenly into its interior. Let it stand at room temperature for 30-45 minutes to obtain a gel plate. 4) Cover the gel plate with aluminum-plastic film and seal three sides of the gel plate with a heat sealer. Then place the gel plate with the aluminum-plastic film-sealed three sides in a vacuum drying oven and vacuum dry for 9 minutes. Take it out and seal the fourth side of the gel plate with a heat sealer to complete the encapsulation, and obtain a solid composite phase change thermal insulation material of alumina and ceramic fiber felt.
[0029] Example 4: 1) Mix aluminum chloride hexahydrate, anhydrous ethanol, and deionized water in a beaker at a mass ratio of 5:9:9 to form a mixture, and then hydrolyze by ultrasonic stirring for 1-2 hours. 2) Add propylene oxide to the ultrasonically treated mixture, with a mass ratio of propylene oxide to deionized water of 9:9. Stir for 1 to 3 minutes and then stop to allow the mixture to gel. 3) Pour the gelled mixture onto the ceramic fiber felt, allowing the mixture to wet the surface of the ceramic fiber felt and penetrate evenly into its interior. Let it stand at room temperature for 30-45 minutes to obtain a gel plate. 4) Cover the gel plate with aluminum-plastic film and seal three sides of the gel plate with a heat sealer. Then place the gel plate with the aluminum-plastic film-sealed three sides in a vacuum drying oven, vacuum dry for 2 minutes, take it out, and seal the fourth side of the gel plate with a heat sealer to complete the encapsulation, thus obtaining a solid composite phase change thermal insulation material of alumina and ceramic fiber felt.
[0030] The following are the measurements of the performance parameters of a lightweight, high-thermal-insulation-performance, and low-cost solid composite phase change thermal insulation material (Example 1) made of alumina and ceramic fiber felt prepared according to the present invention: like Figure 4 As shown, the enthalpy value was measured by simultaneous thermal analysis (STA) combined with thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). The measured enthalpy value of the phase change material was 1682 J / g, which proves that the phase change material of the present invention has good heat absorption performance and also fully combines the heat absorption performance of the phase change insulation material at medium temperature.
[0031] like Figure 5 As shown, the sample was placed on a 500-degree Celsius heating stage, with a temperature recorder placed on both the front and back of the sample to record the temperature. Pressure was applied to the sample for hot and cold surface analysis. Figure 5 The results show that when the hot side of the phase change insulation material reaches 500°C, its cold side is only about 150°C, perfectly demonstrating the excellent high-temperature insulation performance of the phase change insulation material.
[0032] The temperature difference between the hot and cold surfaces of the phase change insulation material is as follows: Figure 6 As shown in Table 1, some data on the temperature difference between the hot and cold surfaces of the sample were analyzed. According to the data, the temperature difference between the hot and cold surfaces of the phase change insulation material can reach up to 376.7℃ at high temperatures, which further proves the good high-temperature insulation performance of the phase change insulation material.
[0033] Table 1. Detection data of temperature difference between hot and cold surfaces of the phase change material of the present invention. In addition, the thermal insulation performance of the solid composite phase change thermal insulation material prepared by this invention (Example 1) was tested and compared with that of several other materials. The results are shown in Table 2 and... Figure 7 As shown.
[0034] Table 2 Comparison of the detection data of the hot and cold surface temperature difference between the material of the present invention and other materials. From Table 2 and Figure 7The comparison results show that the material of the present invention has an absolute advantage in terms of the temperature difference between the hot and cold surfaces compared with other traditional materials. The temperature difference between the hot and cold surfaces can reach 376.7°C in 600 seconds at high temperature, which shows very good high temperature insulation performance.
[0035] The enthalpy values of the solid composite phase change thermal insulation material prepared by this invention (Example 1) compared with those of several other materials are shown in Table 3 below.
[0036] Table 3. Comparison of enthalpy values of the material of the present invention with other materials. As shown in Table 3, the enthalpy of the solid composite phase change thermal insulation material of the present invention is 1682 J / g, while the enthalpy of other materials is between 60 and 120 J / g. This indicates that the enthalpy of the solid composite phase change thermal insulation material prepared by the present invention is much greater than that of other materials. A higher enthalpy value means a stronger heat absorption capacity, and more heat is absorbed when the power battery experiences thermal runaway. Therefore, the solid composite phase change thermal insulation material of the present invention greatly reduces the risk of battery thermal propagation, and can significantly improve the battery's service life and safety performance.
[0037] like Figure 8 As shown, a 1.2 mm thick thermal propagation-inhibiting composite phase change insulation material was prepared using the method of this invention. A simulation diagram is shown below. Figure 8 As shown, T1 and T2 represent the temperatures of the left and right sides of cell 1, T3 and T4 represent the temperatures of the left and right sides of cell 2, and T5 and T6 represent the temperatures of the left and right sides of cell 3. Figure 9 A thermal runaway suppression test was conducted. The test involved securing three intact 314Ah battery cells with a clamp using a force of 1300N. The composite phase change heat insulation material of this invention was placed between each cell. Following the requirements of national standard 36276, the middle cell (cell #2) was overcharged to trigger thermal runaway. The test observed whether thermal runaway occurred, leading to fires and explosions in the cells on either side. If no fires or explosions occurred in either side of the cells after two hours of observation, it demonstrates that the composite phase change heat insulation material of this invention effectively prevents thermal runaway from the battery. The test results are as follows: Figure 10 As shown, by Figure 10 It can be seen that T3 and T4 are the highest temperatures generated by the thermal runaway cells, and T2 and T5 are the highest temperatures of adjacent cells. The results show that the composite phase change thermal insulation material of the present invention did not experience thermal propagation.
[0038] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the present invention as claimed. The scope of protection of this invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a solid composite phase change thermal insulation material, characterized in that, Includes the following steps: S1: Take inorganic aluminum salt, anhydrous ethanol and deionized water in proportion to form a mixture, and then treat the mixture with ultrasound. S2: Add gel initiator to the ultrasonically treated mixture in proportion, and stir to gel the mixture; S3: A gel plate is obtained by combining a gelled mixture with ceramic fiber felt; S4: Cover and package the gel plate with aluminum-plastic film, vacuum process it and then seal it to obtain a solid composite phase change thermal insulation material.
2. The method for preparing a solid composite phase change thermal insulation material according to claim 1, characterized in that, In step S1, the mass ratio of inorganic aluminum salt: anhydrous ethanol: deionized water is 4~5:5~9:3~12.
3. The method for preparing a solid composite phase change thermal insulation material according to claim 2, characterized in that, In step S1, the mass ratio of inorganic aluminum salt: anhydrous ethanol: deionized water is 4:5:
12.
4. The method for preparing a solid composite phase change thermal insulation material according to claim 3, characterized in that, In step S1, the ultrasonic treatment time is 1~2 hours.
5. The method for preparing a solid composite phase change thermal insulation material according to claim 4, characterized in that, In step S2, the gel initiator is propylene oxide, wherein the mass ratio of propylene oxide to deionized water is 5~9:3~12.
6. The method for preparing a solid composite phase change thermal insulation material according to claim 5, characterized in that, Step S3, the step of combining the gelled mixture with the ceramic fiber felt, includes: S31: Pour the gelled mixture onto the ceramic fiber felt, so that the mixture wets the surface of the ceramic fiber felt and penetrates it evenly into its interior; S32: Let the obtained ceramic fiber felt permeated with the mixed solution stand at room temperature for 30-45 minutes to obtain a gel plate.
7. The method for preparing a solid composite phase change thermal insulation material according to claim 6, characterized in that, Step S4, the steps for obtaining the solid composite phase change thermal insulation material include: S41: Cover the gel plate with aluminum-plastic film and seal three sides of the gel plate with a heat sealer; S42: Place the gel plate with three sides sealed by aluminum-plastic film in a vacuum drying oven and vacuum dry for 2-9 minutes; S43: After drying, remove the gel plate and seal its fourth side with a heat sealer to complete the encapsulation, thus obtaining a solid composite phase change thermal insulation material.
8. A solid-state composite phase change thermal insulation material, characterized in that, The solid composite phase change thermal insulation material is obtained by the preparation method according to any one of claims 1-7.
9. The application of a solid composite phase change thermal insulation material according to claim 8 in a battery insulation system.